1989
DOI: 10.1111/j.1751-1097.1989.tb05578.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of the (6–4) Photoproduct

Abstract: The (6-4) photoproduct is an important determinant of the lethal and mutagenic effects of UV irradiation of biological systems. The removal of this lesion appears to correlate closely with the early DNA repair responses of mammalian cells, including DNA incision events, repair synthesis and removal of replication blocks. The processing of (6-4) photoproducts and cyclobutane dimers appears to be enzymatically coupled in bacteria and most mammalian cell lines examined (i.e. a mutation affecting the repair of one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
292
0
5

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(308 citation statements)
references
References 101 publications
11
292
0
5
Order By: Relevance
“…This also indicates that these treatments may induce DNA-strand breaks in plant tissues. In human skin, DNA-strand breaks constitute a considerable portion of the lesions caused by UV-B and UV-A exposure [38]. However, yeast elicitor did not cause increased levels of the nicotinamide metabolites nicotinic acid-N-glucoside and/or trigonelline in cell suspensions cultures of N. tabacum [39].…”
Section: Different Signal Systems Depending On the Type Of Stressor?mentioning
confidence: 99%
“…This also indicates that these treatments may induce DNA-strand breaks in plant tissues. In human skin, DNA-strand breaks constitute a considerable portion of the lesions caused by UV-B and UV-A exposure [38]. However, yeast elicitor did not cause increased levels of the nicotinamide metabolites nicotinic acid-N-glucoside and/or trigonelline in cell suspensions cultures of N. tabacum [39].…”
Section: Different Signal Systems Depending On the Type Of Stressor?mentioning
confidence: 99%
“…Based on sequence comparisons, these genes encode DNA photolyases specific for cyclobutane pyrimidine dimers (CPDs), and it has been suggested that these genes are involved in viral DNA repair (van Oers et al, 2005). CPDs as well as pyrimidine 6-4 pyrimidone photoproducts [(6-4)PP] are formed upon exposure of genomic DNA to UV light (UVB, 280-320 nm), but CPDs constitute the majority of UV-induced DNA lesions (Mitchell & Nairn, 1989;Rycyna & Alderfer, 1985;Setlow & Carrier, 1966). Dimeric pyrimidine photoproducts are cytotoxic, as they block transcription, may induce mutations and trigger apoptosis (Ljungman & Zhang, 1996;Nishigaki et al, 1998;Chiganças et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although both the pyrimidine (6-4)pyrimidone photoproduct [ adduct], which is one of the major classes of UV-induced DNA photoproducts (9,10), and its Dewar valence isomer (Dewar product) (Fig. 1A) cause mutations during TR, their mutagenic properties differ.…”
mentioning
confidence: 99%